MANAJEMEN PENGELOLAAN ZAKAT PRODUKTIF DALAM PERSPEKTIF BANK ISLAM - Agus Riyadi (Ekonomi Syariah IAIN Kudus, 2014)
Tulisan ini menganalisis tentang peluang pengelolaan zakat melalui bank syariah. Zakat produktif disadari memiliki peranan penting dalam mengentaskan kemiskinan dari pada zakat konsumtif. Argument tulisan ini adalah bahwa zakat produtif akan lebih efektij jika dikelola oleh bank syariah. Sebagai institusi berbasis Islam, bank syariah bisa mengelola dana zakat dengan produk bank yang bebas riba. Lembaga dan organisasi perbankan syariah yang sehat akan mampu mengelola zakat secara professional. Proses pengelolaan zakat produktif bisa dilakukan dengan tiga cara: penerima zakat menjadi kreditur dan debitur sekaligus; transaksi dicatat dalam sistem bagi hasil; zakat diserahkan secara penuh.Kata Kunci: Menejemen, Zakat, Perbankan.MANAGEMENT OF PRODUCTIVE ZAKAT IN THE PERSPECTIVE OF ISLAMIC BANKING. This article analyzes the probability of zakat management by sharia banking. Productive Zakat considered having a big role in alleviating poverty than consumptive zakat. This article argues that it will be more effective if administered by Islam banking. Islam banking as an economic missionary institution can manage productive zakat through banking products free of usury. Moreover, a good organization and balance of Islamic banking makes it potential to manage zakat professionally. The management process of productive zakat can be done by three alternatives; the recipient of zakat at the same time serves as creditor as well as debtor, creditor clients are included in the transaction of profit share, or that the zakat of debtor under the bank assistance is fully given.Keywords: Management, Zakat, Banking.